The Concept of Entrepreneurship and Entrepreneur Model of Muslimpreneurs: Theories and Practices - Sutrisno Sutrisno; Razali Haron (Unisia, 2021)
Research on the role of religion in motivating entrepreneurship and the practice of successful entrepreneurs, especially for Muslims, is rarely done. This paper will complement existing entrepreneurial theories by comparing entrepreneurship Islamic perspective and the practices that have been carried out by Muslimpreneurs in the theories and practices. Furthermore, this paper discusses the basic principles of entrepreneurship and entrepreneurship Islamic perspective compared to the Muslimpreneurs today. This paper outlines how Islam forms entrepreneurship at the level of basic spirit, motivation, and practices that are carried out to show that Islam provided the theories of entrepreneurship and practice at the level of primary motivation in implementation. This article explains potential connections affecting entrepreneurial actions and business theory from Muslimpreneur's Islamic perspective. In addition, this paper seeks to bridge and encourage the success of Muslimpreneurs in business with a spirit and religious motivation approach